DISCURSIVE FEATURES OF TEXTUAL ANALYSIS OF I.YUSUPOV’S POETRY TRANSLATION - Mamirbaeva, D.; Aymanova, Sh. (FAN va JAMIYAT, 2019)
The given article is devoted to the problem of discursive analysis of the works of the Karakalpak poet I.Yusupov in translation into English and some approaches of transferring a sense of titles’ taking into account the author’s intention.